Optimizing Seed Priming Techniques to Enhance Growth and Yield Traits in Sunflower (Helianthus annuus L.) - RAKSHITHA HN; PARASHIVAMURTHY; MS HARISH; B BASAVARAJA (Seed Research, 2025)
Seed priming is one of the economical and feasible technologies for uniform crop development in most of the field crops. This technique is very important as a pre-sowing practice in oil seed crops that easily lose vigour during storage. The present investigation aimed to optimize seed priming technique in Indian sunflower genotypes. The field experiment was conducted in ‘J’ Block, AICRP on Seed (Crops), NSP, University of Agricultural Sciences, GKVK, Bangalore. Out of 6 priming treatments, the treatment hydropriming for 18 h was recorded higher growth and yield parameters viz., field emergence (76.94%), plant height (37.50, 110.95 and 140.68 cm at 30, 45 and 60 DAS), number of leaves (13.32, 19.32 and 23.56 at 30, 45 and 60 DAS), days to first flowering (49.20), days to 50% flowering (55.20). Highest capitulum diameter (20.77 cm), total number of achenes per capitulum (1842.62) and yield per plant (46.47 g) was recorded in hydropriming for 18 h followed by priming with 2% KNO3 for 18 h (19.32 cm, 1779.99 and 45.68 g, respectively). Hence, it is concluded that hydropriming for 18 h and priming with 2% KNO3 for 18 h had a major impact on growth and yield in sunflower.